La manzana de piedra de Albalucía Ángel: entre “Barbazul” y el desmantelamiento de paradigmas patriarcales - Garavito, Lucía (Latin American Theatre Review, 2010)
La manzana de piedra, an unpublished play by Angel, fits into the category of textsthat explore “writing beyond the ending” (Rachel Blau DuPlessis). It unmasks and deconstructscultural forms responsible for women’s oppression while reformulating a new femininesubject, free of the constraints imposed by family, community and tradition. “Barbazul” andthe forbidden chamber motif provide the subtext for the exploration of domestic violence asexperienced by women generation after generation. Virginia Woolf’s room of one’s own, onthe other hand, represents for Angel the possibility of a transgressive, creative and criticalspace where women can propose their own way of being and doing in today’s world. (LG,Article in Spanish)